95 aluminum oxide ceramic for vacuum switch and preparation method of 95 aluminum oxide ceramic

By improving the raw material formula and preparation process of high alumina ceramics, combining nano and micron α-alumina, yttrium oxide, lanthanum oxide, fused silica, magnesium fluoride and Suzhou soil, the problem of insufficient performance of high-voltage vacuum switch tubes is solved, and the performance of high-voltage vacuum switch tubes is achieved. The high mechanical strength, insulation performance and chemical stability of ceramics meet the strict requirements of high-pressure vacuum tubes, extends service life and reduces maintenance costs.

CN119161173APending Publication Date: 2024-12-20JINGDEZHEN LEADING SPECIAL CERAMICS CO LTD

Patent Information

Application Number
CN202411359491.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing high alumina ceramics are insufficient in high-voltage vacuum switch tubes and cannot meet the requirements of higher insulation performance, pressure resistance, wear resistance, corrosion resistance and stability, resulting in short service life and high maintenance costs.

Method used

Nanoα-alumina and microα-alumina are used to form the basic raw material, and yttrium oxide, lanthanum oxide, fused silica, magnesium fluoride and Suzhou soil are added. By improving the raw material formula and preparation process, two sintering treatments are carried out to reduce the sintering temperature. , improve the density and mechanical strength of ceramics, enhance insulation performance and thermal shock resistance, reduce pores, and improve chemical stability.

Benefits of technology

The prepared 95 alumina ceramic has excellent flexural strength, electric breakdown strength, thermal shock resistance and chemical stability, which meets the strict performance requirements of high-voltage vacuum tubes, extends service life and reduces maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses 95 aluminum oxide ceramic for a vacuum switch and a preparation method of the 95 aluminum oxide ceramic, and belongs to the technical field of aluminum oxide ceramic and vacuum switches. The ceramic disclosed by the invention is prepared from the following raw materials: 3 to 5 parts of nano alpha-aluminum oxide, 0.05 to 0.1 part of yttrium oxide, 0.04 to 0.08 part of lanthanum oxide, 0.3 to 0.6 part of zirconium silicate, 3.0 to 4.5 parts of fused quartz, 1 to 1.6 parts of magnesium fluoride, 0.3 to 0.5 part of calcium carbonate, 0.3 to 0.5 part of barium carbonate, 1.5 to 2.5 parts of Suzhou clay and 93 to 94 parts of micron alpha-aluminum oxide. The prepared high-performance 95 aluminum oxide ceramic has excellent breaking strength, electric breakdown strength, thermal shock resistance, chemical stability and the like, can meet the performance requirements of a high-pressure vacuum tube in a severe working environment, and ensures the working stability of a circuit.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of alumina ceramics and vacuum switches, and specifically relates to a 95 alumina ceramic for a vacuum switch and a preparation method thereof. Background Art

[0002] Vacuum switch tubes are the core components of medium and high voltage power switches. Through the excellent insulation of the vacuum inside the tube, the medium and high voltage circuits can quickly extinguish arcs and suppress current after the power is cut off, thus avoiding accidents and unexpected events. Currently, they are widely used in many fields such as electricity, metallurgy, mining, petrochemicals, and railways.

[0003] With the rapid development of industrial technology and the continuous progress of the power industry, high-voltage vacuum switch tubes, as an important part of the power system, have great significance for ensuring the safe and efficient operation of the power grid in terms of performance stability and reliability. However, with the increasing complexity of the power system and the continuous increase in power load, the performance requirements for high-voltage vacuum switch tubes have become more stringent. As a key component for controlling and protecting circuits, the core function of high-voltage vacuum switch tubes is to achieve rapid switching of circuits and maintain stable performance under extreme conditions. In this process, the material selection of the insulating shell has a decisive influence on the performance of the switch tube. At present, high-voltage vacuum switch tubes generally use high-alumina ceramics as the insulating shell material. Its excellent high-temperature stability, good insulation and corrosion resistance make it an ideal material choice.

[0004] However, with the development of power technology and the increase of power load, the performance of conventional high-alumina ceramics has gradually failed to meet the increasingly stringent performance requirements of high-voltage vacuum switches. On the one hand, higher rated voltages and rated currents require the insulating shell material to have higher insulation performance and stronger pressure resistance; on the other hand, in pursuit of longer service life and lower maintenance costs, higher requirements are also placed on the material's wear resistance, corrosion resistance and stability.

[0005] In view of this, further research and improvement are still needed on the existing high alumina ceramic formula for the insulating shell of vacuum switch tubes. Summary of the invention

[0006] In view of the problems raised in the background technology, the present invention provides a 95 alumina ceramic for vacuum switch and a preparation method thereof. By improving the raw material formula and preparation process, the present invention obtains ceramics with excellent flexural strength, electrical breakdown strength, thermal shock resistance and chemical stability, meeting the performance requirements of high-voltage vacuum switch.

[0007] In order to achieve the above object, the present invention specifically adopts the following technical solutions: The present invention provides a 95 alumina ceramic for a vacuum switch, which comprises the following raw materials by weight: 3-5 parts of nano α-alumina, 0.05-0.1 parts of yttrium oxide, 0.04-0.08 parts of lanthanum oxide, 0.3-0.6 parts of zirconium silicate, 3.0-4.5 parts of fused quartz, 1-1.6 parts of magnesium fluoride, 0.3-0.5 parts of calcium carbonate, 0.3-0.5 parts of barium carbonate, 1.5-2.5 parts of Suzhou soil, and 93-94 parts of micron α-alumina.

[0008] Furthermore, the 95 alumina ceramic for vacuum switch includes the following raw materials by weight: 4 parts of nano α-alumina, 0.08 parts of yttrium oxide, 0.06 parts of lanthanum oxide, 0.5 parts of zirconium silicate, 3.8 parts of fused quartz, 1.4 parts of magnesium fluoride, 0.4 parts of calcium carbonate, 0.4 parts of barium carbonate, 2.2 parts of Suzhou soil, and 93.6 parts of micron α-alumina.

[0009] Furthermore, the particle size of the nano-α-alumina is 100-600 nm, and the particle size of the micron-α-alumina is 3-5 μm.

[0010] Furthermore, the mass ratio of yttrium oxide to lanthanum oxide is 1-1.5:1.

[0011] The present invention also provides a method for preparing the above-mentioned 95 alumina ceramic for vacuum switch, comprising the following steps: Step 1: weighing each raw material according to the formula ratio, taking nano α-alumina, yttrium oxide, lanthanum oxide, zirconium silicate, fused quartz, magnesium fluoride, calcium carbonate, barium carbonate, and Suzhou soil, ball milling and mixing to obtain a small material, and performing a sintering treatment on the small material; Step 2: adding the sintered small material obtained in step 1 to micron α-alumina and mixing by ball milling to obtain a mixture, spray granulating the mixture to obtain alumina granulated powder, and then pressing to obtain a ceramic body; Step 3: performing secondary sintering on the obtained ceramic body to obtain a finished ceramic product.

[0012] Furthermore, in step 2, the particle size of the alumina granulated powder is 20-140 μm, and the pressing pressure is 100-150 MPa.

[0013] Furthermore, the temperature of the first sintering treatment in step 1 is 1100-1400° C., the heating rate is 8-12° C. / min, and the holding time is 1-2 h; the sintering atmosphere of the first sintering treatment is oxygen.

[0014] Furthermore, the temperature of the secondary sintering treatment in step 3 is 1600-1800° C., the heating rate is 4-5° C. / min, and the holding time is 2-3 h; the sintering atmosphere of the second sintering treatment is oxygen.

[0015] Compared with the prior art, the present invention has the following beneficial effects: In view of the increasingly stringent performance requirements of vacuum switch tubes, the present invention further optimizes the defects of mechanical properties, thermal shock resistance, insulation and other performances of conventional alumina ceramics by improving the raw material formula. The present invention uses nano-α-alumina and micron-α-alumina as the basic raw materials, adds yttrium oxide and lanthanum oxide: reduces the sintering temperature, improves the density and mechanical strength of the ceramic, forms a glass phase at the grain boundary, generates intergranular compounds to strengthen the grain boundary bonding strength, and improves the insulation performance and breakdown strength of the ceramic, adds fused quartz: improves the thermal shock resistance and corrosion resistance of the ceramic, optimizes the ceramic structure, adds magnesium fluoride: promotes sintering, inhibits grain growth, increases grain boundary energy, and improves the microstructure, and adds Suzhou soil: further improves the thermal shock resistance of the ceramic and promotes compactness; the present invention also uses two sintering processes, and by controlling the corresponding processing parameters and sintering atmosphere, the pores in the matrix are greatly reduced, and the chemical stability and electrical breakdown strength are further improved.

[0016] The high-performance 95 alumina ceramics prepared by the present invention have excellent flexural strength, electrical breakdown strength, thermal shock resistance and chemical stability, etc., can meet the performance requirements of the harsh working environment of high-voltage vacuum tubes, and ensure the stability of circuit operation. DETAILED DESCRIPTION

[0017] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0018] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0019] The main components of the Suzhou soil used in the following experiments of the present invention are: SiO2 46.32%, Al2O3 38.77%, Fe2O3 3.03%, CaO 1.14%, MgO 3.21%, and R2O 4.54%; the main components of the mixed bentonite used are: SiO2 49.83%, Al2O3 31.54%, Fe2O3 1.72%, CaO 7.28%, MgO 2.36%, and R2O 6.15%.

[0020] Example 1 A method for preparing 95 alumina ceramics for vacuum switches, comprising: 1. Accurately weigh 4 parts of nano-α-alumina (100-600 nm), 0.08 parts of yttrium oxide, 0.06 parts of lanthanum oxide, 0.5 parts of zirconium silicate, 3.8 parts of fused quartz (99.9%), 1.4 parts of magnesium fluoride, 0.4 parts of calcium carbonate, 0.4 parts of barium carbonate, 2.2 parts of Suzhou soil, and 93.6 parts of micron α-alumina (3-5 μm) by weight.

[0021] 2. Take nano-α-alumina, yttrium oxide, lanthanum oxide, zirconium silicate, fused quartz, magnesium fluoride, calcium carbonate, barium carbonate, and Suzhou soil and add them to a ball mill. Mix and ball-mill for 0.5 h to obtain small materials. Transfer the small materials into an oxygen atmosphere and carry out the first sintering treatment. Heat to 1260°C at a heating rate of 10°C / min, and then keep warm for 1.5 h.

[0022] 3. Take out the sintered small material and crush it, add it to the micron α-alumina and mix it, transfer it to a ball mill for mixing and ball milling for 3 hours to obtain a mixture, transfer the mixture to a spray granulation tower, and spray granulate it into alumina granulated powder with a particle size of 20-140 μm; add the alumina granulated powder into a mold, and use an isostatic press to press it into a ceramic body at a pressure of 120 MPa; turn the isostatically pressed ceramic body to the specified size through a precision lathe, and then heat it to 200℃ for preheating for 30 min, transfer it to an oxygen atmosphere, and carry out a second sintering treatment, heating it to 1720℃ at a heating rate of 4℃ / min, and then keep it warm for 2.5 hours to obtain a ceramic product.

[0023] Example 2 A method for preparing 95 alumina ceramics for vacuum switches, comprising: 1. Accurately weigh 3 parts of nano-α-alumina (100-600 nm), 0.1 parts of yttrium oxide, 0.08 parts of lanthanum oxide, 0.3 parts of zirconium silicate, 4.5 parts of fused quartz (99.9%), 1.6 parts of magnesium fluoride, 0.3 parts of calcium carbonate, 0.5 parts of barium carbonate, 2.5 parts of Suzhou clay, and 94 parts of micron α-alumina (3-5 μm) by weight.

[0024] 2. Add nano-α-alumina, yttrium oxide, lanthanum oxide, zirconium silicate, fused quartz, magnesium fluoride, calcium carbonate, barium carbonate, and Suzhou soil into a ball mill, mix and ball-mill for 0.5 h to obtain small materials, transfer the small materials into an oxygen atmosphere, and carry out the first sintering treatment at a heating rate of 10°C / min to 1150°C, and then keep warm for 2 h.

[0025] 3. Take out the sintered small material and crush it, add it to micron α-alumina and mix it, transfer it to a ball mill for mixing and ball milling for 3 hours to obtain a mixture, transfer the mixture to a spray granulation tower, and spray granulate it into alumina granulated powder with a particle size of 20-140 μm; add the alumina granulated powder into a mold, and use an isostatic press to press it into a ceramic body at a pressure of 150 MPa; turn the isostatically pressed ceramic body to the specified size through a precision lathe, and then heat it to 200℃ for preheating for 30 min, transfer it to an oxygen atmosphere, and carry out a second sintering treatment, heating it to 1640℃ at a heating rate of 5℃ / min, and then keep it warm for 3 hours to obtain a ceramic product.

[0026] Example 3 A method for preparing 95 alumina ceramics for vacuum switches, comprising: 1. Accurately weigh 5 parts of nano-α-alumina (100-600 nm), 0.05 parts of yttrium oxide, 0.05 parts of lanthanum oxide, 0.6 parts of zirconium silicate, 3 parts of fused quartz (99.9%), 1 part of magnesium fluoride, 0.5 parts of calcium carbonate, 0.3 parts of barium carbonate, 1.5 parts of Suzhou clay, and 93 parts of micron α-alumina (3-5 μm).

[0027] 2. Take nano-α-alumina, yttrium oxide, lanthanum oxide, zirconium silicate, fused quartz, magnesium fluoride, calcium carbonate, barium carbonate, and Suzhou soil and add them to a ball mill. Mix and ball-mill for 0.5 h to obtain small materials. Transfer the small materials into an oxygen atmosphere and carry out the first sintering treatment. Heat to 1380°C at a heating rate of 8°C / min, and then keep warm for 1 h.

[0028] 3. Take out the sintered small material and crush it, add it to the micron α-alumina and mix it, transfer it to a ball mill for mixing and ball milling for 3 hours to obtain a mixture, transfer the mixture to a spray granulation tower, and spray granulate it into alumina granulated powder with a particle size of 20-140 μm; add the alumina granulated powder into a mold, and use an isostatic press to press it into a ceramic body at a pressure of 100 MPa; turn the isostatically pressed ceramic body to the specified size through a precision lathe, and then heat it to 200℃ for preheating for 30 min, transfer it to an oxygen atmosphere, and carry out a second sintering treatment, heating it to 1780℃ at a heating rate of 4℃ / min, and then keep it warm for 2 hours to obtain a ceramic product.

[0029] Comparative Example 1 Refer to the step parameters in Example 1, except that lanthanum oxide is not added to the ceramic raw materials; the raw material amounts are: 4 parts of nano α-alumina (100-600 nm), 0.14 parts of yttrium oxide, 0.5 parts of zirconium silicate, 3.8 parts of fused quartz, 1.4 parts of magnesium fluoride, 0.4 parts of calcium carbonate, 0.4 parts of barium carbonate, 2.2 parts of Suzhou soil, and 93.6 parts of micron α-alumina (3-5 μm).

[0030] Comparative Example 2 Refer to the step parameters in Example 1, except that ordinary high-purity quartz sand (99.9%) is used instead of fused quartz.

[0031] Comparative Example 3 The step parameters are as in Example 1, except that magnesium fluoride is not added to the ceramic raw material.

[0032] Comparative Example 4 Refer to the step parameters in Example 1, except that mixed bentonite is used instead of Suzhou clay.

[0033] Comparative Example 5 Refer to the step parameters in Example 1, except that one sintering process is used instead of two sintering processes.

[0034] The samples prepared in the above embodiments and comparative examples were subjected to performance testing (GB / T 5593-2015 A-95), and the results are shown in the following table.

[0035]

[0036] In summary, the alumina ceramics prepared in the embodiment of the present invention have excellent flexural strength, electrical breakdown strength, thermal shock resistance and chemical stability, can adapt to the increasingly stringent performance requirements of high-voltage vacuum switches, improve service life and reduce maintenance costs, and the preparation method is simple and suitable for industrial production.

[0037] The embodiments described above only express several preferred embodiments of the present invention, and the descriptions thereof are relatively specific and detailed, but are not intended to limit the present invention. It should be noted that for those skilled in the art, the present invention may also have various changes and modifications, and any modifications, equivalent substitutions, improvements, etc. made within the concept and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A 95 alumina ceramic for vacuum switch, It is characterized in that The following raw materials are included by weight: 3-5 parts of nano α-alumina, 0.05-0.1 parts of yttrium oxide, 0.04-0.08 parts of lanthanum oxide, 0.3-0.6 parts of zirconium silicate, 3.0-4.5 parts of fused quartz, 1-1.6 parts of magnesium fluoride, 0.3-0.5 parts of calcium carbonate, 0.3-0.5 parts of barium carbonate, 1.5-2.5 parts of Suzhou soil, and 93-94 parts of micron α-alumina.

2. The 95 alumina ceramic for vacuum switch according to claim 1, It is characterized in that The 95 alumina ceramic for vacuum switch includes the following raw materials by weight: 4 parts of nano α-alumina, 0.08 parts of yttrium oxide, 0.06 parts of lanthanum oxide, 0.5 parts of zirconium silicate, 3.8 parts of fused quartz, 1.4 parts of magnesium fluoride, 0.4 parts of calcium carbonate, 0.4 parts of barium carbonate, 2.2 parts of Suzhou soil, and 93.6 parts of micron α-alumina.

3. The 95 alumina ceramic for vacuum switch according to claim 1, It is characterized in that The particle size of the nano-α-alumina is 100-600 nm, and the particle size of the micron-α-alumina is 3-5 μm.

4. The 95 alumina ceramic for vacuum switch according to claim 1, It is characterized in that The mass ratio of yttrium oxide to lanthanum oxide is 1-1.5:

1.

5. A method for preparing 95% alumina ceramic for vacuum switch according to any one of claims 1 to 4, It is characterized in that The steps include: Step 1: weighing each raw material according to the formula ratio, taking nano α-alumina, yttrium oxide, lanthanum oxide, zirconium silicate, fused quartz, magnesium fluoride, calcium carbonate, barium carbonate, and Suzhou soil, ball milling and mixing to obtain a small material, and performing a sintering treatment on the small material; Step 2: adding the sintered small material obtained in step 1 to micron α-alumina and mixing by ball milling to obtain a mixture, spray granulating the mixture to obtain alumina granulated powder, and then pressing to obtain a ceramic body; Step 3: performing secondary sintering on the obtained ceramic body to obtain a finished ceramic product.

6. The method for preparing 95% alumina ceramic for vacuum switch according to claim 5, It is characterized in that In step 2, the particle size of the alumina granulated powder is 20-140 μm, and the pressing pressure is 100-150 MPa.

7. The method for preparing 95% alumina ceramic for vacuum switch according to claim 5, It is characterized in that The temperature of the first sintering treatment in step 1 is 1100-1400° C., the heating rate is 8-12° C. / min, and the holding time is 1-2 h; the sintering atmosphere of the first sintering treatment is oxygen.

8. The method for preparing 95% alumina ceramic for vacuum switch according to claim 5, It is characterized in that The temperature of the secondary sintering treatment in step 3 is 1600-1800° C., the heating rate is 4-5° C. / min, and the holding time is 2-3 h; the sintering atmosphere of the second sintering treatment is oxygen.

Citation Information

Patent Citations

  • Preparation method of alumina ceramic

    CN110204315A

  • 99 alumina structural ceramic and preparation method thereof

    CN118206362A

  • Alpha-Al2O3 ceramic for electric vacuum

    CN1340475A

  • Composite cylinder liner preparing technique by reinforcing alumina with zirconia

    CN1990421A

  • Alumina ceramic and ignition plug

    JP1988190753A

Cited By

  • Alumina ceramic with low thermal expansion coefficient and preparation method thereof

    CN120903917A

  • Ceramic shell for low-power protective tube and preparation method of ceramic shell

    CN122301542A